2020
DOI: 10.32799/ijih.v15i1.33985
|View full text |Cite
|
Sign up to set email alerts
|

Cree Youth Engagement in Health Planning

Abstract: Indigenous communities experience a greater burden of ill health than all other communities in Canada. Across the (Indigenous Region), all nine (Name) communities experience similar health challenges. In 2014, the (REGIONAL_BOARD) supported an initiative to stimulate local community prioritization for health change. While many challenges identified were specific to youth (10-29 years of age), youth’s perspectives in these reports to date have been limited. We sought to understand how (Indigenous) youth perceiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(24 citation statements)
references
References 19 publications
0
24
0
Order By: Relevance
“… The youth described body mapping as a valid data collection tool that advanced and promoted trust and youth voices in research while reducing verbal communication barriers and facilitating the collection of rich data on Indigenous youth experiences Youth affirmed that using the body mapping in FOXY encouraged and supported wellness and healing through self-reflection, introspection leading to self-discovery, and personal/cultural connectedness while enhancing the ability to process difficult emotions. The authors reported that directions for future research could explore repeat exposure to body mapping interventions and their impact on well-being 16 Merati et al, 2020 [ 8 ]. To explore how Cree youth perceived youth health and youth engagement in health and health planning.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“… The youth described body mapping as a valid data collection tool that advanced and promoted trust and youth voices in research while reducing verbal communication barriers and facilitating the collection of rich data on Indigenous youth experiences Youth affirmed that using the body mapping in FOXY encouraged and supported wellness and healing through self-reflection, introspection leading to self-discovery, and personal/cultural connectedness while enhancing the ability to process difficult emotions. The authors reported that directions for future research could explore repeat exposure to body mapping interventions and their impact on well-being 16 Merati et al, 2020 [ 8 ]. To explore how Cree youth perceived youth health and youth engagement in health and health planning.…”
Section: Discussionmentioning
confidence: 99%
“… Promoting strength-based approaches to youth engagement 19 (95.0) [ 5 , 8 , 16 , 44 , 57 , 71 84 ] 1. Lack of community support (social, financial, organizational for wellness promotion among Indigenous youth) 11 (55.0) [ 5 , 44 , 57 , 72 , 74 78 , 80 , 81 ] 1a Peer-to-peer mentoring (Indigenous youth mentored by, and with other Indigenous youth) 15 (75.0) [ 5 , 8 , 44 , 57 , 71 , 73 76 , 79 84 ] 2. Structural and organizational issues within Indigenous communities with regards to wellness promotion programs 10 (50.0) [ 5 , 8 , 72 , 73 , 76 78 , 81 83 ] 1b Engaging youth in activities that develop and promote self-determination, capacity budling, and empowerment (e.g., guided storyboarding, performative art, arts-based therapy, etc.)…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations